The haunted hotel - Roy, Ron; Gurney, John Steven (New York : Random House, 1999)
When the guests of the Shangri-La Hotel are scared away by a white-haired female ghost, Dink and his friends investigate the mystery.
"A Stepping Stone Book"
Keywords: Ghosts; Hotels, motels, etc; Mystery and detective stories